Dimensions of authority in oversight agencies: American and Australian comparisons - Kempf, Robin J.; Graycar, Adam (2018)
Fraud, waste, and abuse damage public administration. Responding involves law enforcement and best practice administration. Many jurisdictions create watchdog agencies to perform this role. A model, which includes seven dimensions of jurisdiction and authority that policymakers should consider when creating an oversight entity, is presented. The model goes beyond the simple functional jurisdiction, i.e., who is overseen and how oversight occurs. Four subnational watchdog agencies in two countries are examined to demonstrate the trade-offs that occur in each dimension when the agencies are designed. This analysis demonstrates there are significant balancing issues at stake, which impact watchdog effectiveness. - Reproduced.
Keywords: Corruption; Accountability